2013
DOI: 10.1074/mcp.m113.030692
|View full text |Cite
|
Sign up to set email alerts
|

New Arabidopsis thaliana Cytochrome c Partners: A Look Into the Elusive Role of Cytochrome c in Programmed Cell Death in Plants

Abstract: Programmed cell death is an event displayed by many different organisms along the evolutionary scale. In plants, programmed cell death is necessary for development and the hypersensitive response to stress or pathogenic infection. A common feature in programmed cell death across organisms is the translocation of cytochrome c from mitochondria to the cytosol. To better understand the role of cytochrome c in the onset of programmed cell death in plants, a proteomic approach was developed based on affinity chroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
60
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 93 publications
2
60
0
Order By: Relevance
“…The findings can open up new ways to understand the process in organisms that lack Apaf-1 or whose apoptosome is devoid of Cc. Given that Cc is highly concentrated in the mitochondrial intermembrane space and that its release into the cytoplasm is an evolutionarily well-conserved event, it is likely that Cc regulates other metabolic processes during PCD, as has been similarly corroborated in plants (105).…”
Section: Discussionmentioning
confidence: 94%
“…The findings can open up new ways to understand the process in organisms that lack Apaf-1 or whose apoptosome is devoid of Cc. Given that Cc is highly concentrated in the mitochondrial intermembrane space and that its release into the cytoplasm is an evolutionarily well-conserved event, it is likely that Cc regulates other metabolic processes during PCD, as has been similarly corroborated in plants (105).…”
Section: Discussionmentioning
confidence: 94%
“…The organization of the mitochondrial electron transport chain is a subject of intense debate at present, where two different models are being considered: the fluid model, that proposes a random organization for individual respiratory protein components, and the solid model, suggesting a stable association between individual complexes [6][7][8]. Apart their role in respiration, Cc and Cc 1 are clearly involved in the development of programmed cell death [9][10][11][12][13][14][15]. Such a dual role of Cc is regulated by post-translational modifications -namely, phosphorylation and nitration of tyrosine residues -that affect the binding of Cc to its physiological counterparts, either in the mitochondria or in the cytoplasm [16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…In mammalian cells, extramitochondrial Cc interacts with apoptosis activating factor 1 (Apaf-1) in the cytoplasm to spark the caspase proteolytic cascade (15). It has recently been shown that Cc can interact with several other proteins outside the mitochondria in humans and plants (18)(19)(20)(21). The similarities between the Cc signaling networks in both organisms suggest that key programmed cell-death pathways are conserved throughout evolution (22).…”
mentioning
confidence: 99%
“…In addition, Cc aids in controlling ROS levels by oxidizing superoxide anions (11) and exhibiting peroxidase activity (12); the latter, however, also yields lipid peroxidation (13,14). Furthermore, Cc plays a crucial role in programmed cell death, a process that is only partially understood (15)(16)(17)(18)(19)(20)(21). In this context, a fraction of Cc binds and oxidizes cardiolipin (CL) at the internal mitochondrial membrane, thereby facilitating the release of unbound Cc to the cytoplasm (16,17).…”
mentioning
confidence: 99%